Efektivitas Mekanisme Uji Materiil dalam Penyelesaian Sengketa Administrasi: Kajian Putusan Mahkamah Agung Nomor 6/P/HUM/2021 di Provinsi Banten - Febi Pebiantini (Uniku Law Review, 2025)
This article discusses the effectiveness of the judicial review mechanism in resolving administrative disputes. As a country that upholds the rule of law, Indonesia utilizes the judicial review mechanism as a vital tool to ensure that all existing regulations, including regional regulations, are in line with higher legal norms. This article aims to analyze the regulation and implementation of the judicial review mechanism in Supreme Court Decision Number 6/P/HUM/2021 concerning Serang City Regulation Number 11 of 2019 concerning the implementation of tourism businesses and its impact on the resolution of administrative disputes in Banten Province. The research question addresses how the Supreme Court's authority in judicial review is regulated and implemented in that decision. The research method used is normative juridical with a statutory regulatory approach, conceptual, and case study, with qualitative analysis of primary and secondary legal sources. The findings of this study indicate that the Supreme Court found inconsistencies in the substance and procedures for drafting the Regional Regulation, thus declaring several articles in the Regulation invalid. This decision affirms the Supreme Court's crucial role in maintaining legal consistency and has had a significant impact on the practice of regional regulation-making and administrative dispute resolution. The Supreme Court concluded that the judicial review mechanism implemented by the Supreme Court in Decision Number 6/P/HUM/2021 complies with the applicable legal framework. Recommendations: Regional governments and the Regional People's Representative Council (DPRD) need to ensure that each regional regulation is drafted in accordance with higher-level laws and regulations and complies with applicable drafting procedures.